2015
DOI: 10.1177/8755122514568123
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Perceptions

Abstract: Background: Pharmacy education standards highlight the importance of effective communication skills and the use of technology to provide patient care. As technology evolves, pharmacists have opportunities to communicate in different and broader ways. Objective: The objectives of this study were 3-fold: to evaluate student ability to counsel via telepharmacy, to determine if there is a difference in students' abilities to counsel face-to-face or via telepharmacy, and to determine students' perceptions regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…A brief literature search using the key words "telehealth" and "OSCE" and/or "student perceptions of telehealth OSCE" revealed a sparsity of information related to telehealth simulations or OSCEs for pharmacy learners. Skoy and colleagues revealed no difference between students' abilities to successfully provide medication consultation to patients between face-to-face and telehealth encounters [7]. However, students in this study agreed that there were differences in "difficulty, stress, interpreting patient cues, and in maintaining eye contact and tone of voice between the two means of consultation" [7].…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…A brief literature search using the key words "telehealth" and "OSCE" and/or "student perceptions of telehealth OSCE" revealed a sparsity of information related to telehealth simulations or OSCEs for pharmacy learners. Skoy and colleagues revealed no difference between students' abilities to successfully provide medication consultation to patients between face-to-face and telehealth encounters [7]. However, students in this study agreed that there were differences in "difficulty, stress, interpreting patient cues, and in maintaining eye contact and tone of voice between the two means of consultation" [7].…”
Section: Introductionmentioning
confidence: 62%
“…In particular, students identified non-verbal cues as essential for proper interaction in a patient encounter yet struggled to read these cues in the remote setting. Skoy et al explored the comparison of virtual and face-to-face patient encounters and found that students identified differences in "interpreting patient cues, and in maintaining eye contact and tone of voice between the two means of consultation" [7]. To continue remote OSCEs in the future, students may require support developing their verbal and non-verbal communication skills to effectively provide patient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some customers prefer direct interaction with health professionals when addressing their need for medical information [16,18]. However, Skoy et al, when examining pharmacy students' ability to advise customers through telepharmacy solutions, concluded that the students were successful in providing advice through telepharmacy [25].…”
Section: Accessibility Of Medicines and Related Informationmentioning
confidence: 99%
“…Therefore, pharmacists may experience difficulty in integrating clinical skills used for in-person counseling with the virtual environment [ 11 ] because existing skills and resources are often set up to support face-to-face counseling. Without sufficient telepharmacy training, pharmacy students were reported to be more successful at providing face-to-face consultation than via telepharmacy [ 16 ].…”
Section: Introductionmentioning
confidence: 99%